2016
DOI: 10.1007/s40974-016-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of soil erosion in Inabanga watershed (Bohol, Philippines)

Abstract: Analysis of soil redistribution patterns in watershed areas provides information for understanding soil erosion and deposition for implementing management practices to improve agricultural land conditions and reduce sediment loads in river systems. This paper has demonstrated the use of Cesium-137 (137 Cs) in estimating retrospective medium-term soil erosion rates in selected cassava cultivated areas in Pilar, a sub-watershed within the Inabanga watershed. To estimate erosion and deposition rates and elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…On a global scale, Borrelli et al (2017) implemented K values that range from values lower than < 0.01 t h MJ −1 mm −1 to values > 0.04 t h MJ −1 mm −1 . For Europe Panagos et al (2014) found values for the soil erodibility of up to 0.076 t h MJ −1 mm −1 for medium-to finetextured soils. Naipal et al (2015) implemented values for K of 0.08 t h MJ −1 mm −1 for highly erodible volcanic soils.…”
Section: Usle Input Realizations -Ranges Plausibility and Their Commentioning
confidence: 98%
See 1 more Smart Citation
“…On a global scale, Borrelli et al (2017) implemented K values that range from values lower than < 0.01 t h MJ −1 mm −1 to values > 0.04 t h MJ −1 mm −1 . For Europe Panagos et al (2014) found values for the soil erodibility of up to 0.076 t h MJ −1 mm −1 for medium-to finetextured soils. Naipal et al (2015) implemented values for K of 0.08 t h MJ −1 mm −1 for highly erodible volcanic soils.…”
Section: Usle Input Realizations -Ranges Plausibility and Their Commentioning
confidence: 98%
“…The soil erodibility factor K describes the tendency of a soil to erode due to the erosive force of precipitation or surface runoff and can be related to soil physical and chemical properties (Panagos et al, 2014). Direct assessments of the soil erodibility are only available at a plot scale.…”
Section: Estimation Of Usle Model Inputsmentioning
confidence: 99%